The SDGs as an Operational Framework for Post COVID-19 Response and Recovery (2021)
Despite progress on a number of goals, the world was not moving fast enough towards achieving the Sustainable Development Goals in the pre-COVID era. The Decade of Action started with the hit of the COVID-19 crisis, which stressed the urgent need to tackl